Trends in the Utilization of Blood Components in The Intensive Care Unit in A Tertiary Care Hospital - G Neumann, Bethany; Mondal, Rajat; Saha, Debarshi; Anandarama Adiga, Deepa Sowkur; Kumar, Nikhil; Ghosh, Arnab (Journal of Neonatal Surgery, 2025)
Background: Guidelines for component transfusion are often not followed. Risks are also associated with transfusion and vary with different investigators. We evaluated the utilization of blood and its components among intensive care unit (ICU) patients and studied the association between transfusion and increased morbidity and mortality. Methods: Retrospective study on total 250 patients in ICU >24 hours with 694 transfusion events for 7 months. Components (number and type) transfused, length of stay (LOS) in ICU and hospital, complications and mortality were recorded. Results: A total of 250 of 2102 ICU patients were transfused. Of these 516 (31.40%) were packed cell (PC), 415 (25.26%) platelets concentrate (PLTC), 686 (41.76%) were fresh frozen plasma (FFP), totaling 1643 transfusions. Of the PC transfusions, 60(33%) patients had hemoglobin (Hb)<7g/dl and 77(42.3%) had Hb between Hb 7-9g/dl. Sixty-six (26.4%) of 250 patients were transfused with PLTC of which 53(80.3%) had platelet count<20000/cu.mm. There were 120/250(48%) FFP transfusions of which 83(69.2%). Hb ≤ 9.0g/dl for PC, platelets ≤ 20000/cu.mm for PLTC, INR ≥1.6 (PT≥17s) for FFP were the triggers for respective component transfusion. The mortality among the transfused patients is 22.4%(56/250) compared to that 19.8%(248/1852) of the non-transfused (p=0.00001,significant). The transfusion of PC & PLTC together showed 3.76 (odds ratio) times higher mortality than any other component transfused, either singly or in combination. Conclusions: Transfusion triggers largely agreed with other studies. Mortality is significantly associated with transfusion. The ICU stay increased with PC transfusions i.e. the more the ICU stay, the more likely is the increase in patients being severally transfused.